2020
DOI: 10.1002/alz.12069
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative amyloid PET in Alzheimer's disease: the AMYPAD prognostic and natural history study

Abstract: Introduction: The Amyloid Imaging to Prevent Alzheimer's Disease (AMYPAD) Prognostic and Natural History Study (PNHS) aims at understanding the role of amyloid imaging in the earliest stages of Alzheimer's disease (AD). AMYPAD PNHS adds (semi-)quantitative amyloid PET imaging to several European parent cohorts (PCs) to This is an open access article under the terms of the Creative Commons Attribution-NonCommercial License, which permits use, distribution and reproduction in any medium, provided the original wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 45 publications
0
42
0
Order By: Relevance
“…Thus although baseline amyloid burden illustrates the extent of amyloid pathology, rate of change reflects a subject's position in the amyloid accumulation process, enabling the stratification of individu-als according to their placement in the AD disease course and improving risk-profiling efforts. 32 In individuals classified as Aβ− at baseline, only Aβ slope and its interaction with baseline Aβ burden could predict working and semantic memory performance. This illustrates that longitudinal PET measures are able to identify subjects at the beginning of the amyloid accumulation process, even when they are classified as Aβ− at their baseline visit.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Thus although baseline amyloid burden illustrates the extent of amyloid pathology, rate of change reflects a subject's position in the amyloid accumulation process, enabling the stratification of individu-als according to their placement in the AD disease course and improving risk-profiling efforts. 32 In individuals classified as Aβ− at baseline, only Aβ slope and its interaction with baseline Aβ burden could predict working and semantic memory performance. This illustrates that longitudinal PET measures are able to identify subjects at the beginning of the amyloid accumulation process, even when they are classified as Aβ− at their baseline visit.…”
Section: Discussionmentioning
confidence: 95%
“…Therefore, replication of these results in an independent prospective data set is important and already planned within the Amyloid Imaging to Prevent Alzheimer's Disease (AMYPAD) consortium. 32 Fourth, due to the focus on a CU population, the study sample had a relatively limited representation of high Aβ burden levels, and partial volume error (PVE) correction was not performed because considerable atrophy was not expected. In fact, previous work in this data set demonstrated a strong correlation between PVE-corrected and PVE-uncorrected quantitative values, 23 suggesting that this methodological aspect would likely have minimal effect on our results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For this reason, topographically defined distribution and early Aβ accumulation measured by PET may not necessarily agree with histopathology findings. Despite these discrepancies with neuropathology results, several studies have shown the utility of amyloid PET topographical quantification in staging AD [21][22][23], determining the risk of subsequent cognitive decline [23,25], optimal subject selection for anti-amyloid interventional trials [22,42], and reducing sample size in anti-amyloid interventional trials [43,44]. Pascoal et al also showed that the topographical pattern of individuals with MCI that progress to dementia is "traditionally AD-like," while that of non-converters includes more temporal and occipital regions instead [24].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that early-phase data of many specific PET radioligands mimic brain perfusion in healthy subjects and in patients with neurodegenerative disorders. This had been validated in PET imaging studies of Alzheimer's disease [e.g., (34,35)]. Early-phase data from dopaminergic PET tracers such as 18 F-FDOPA (15), 11 C-raclopride (20), or DAT tracers such as 11 C-PE2I (21) can similarly be used to compute PDRP and PDCP expression in individual subjects.…”
Section: Discussionmentioning
confidence: 99%